Dilema Pemerintah Indonesia Menolak Repatriasi WNI Eks ISIS: Antara HAM atau Keamanan Nasional [The Dilemma of Indonesian Government Rejecting The Repatriation Indonesian Ex-ISIS: Between Human Right or National Security] - Kamarullah, Muhammad (Jurnal Politica, 2023)
This research aims to analyze the Indonesian government’s policy of rejecting repatriate Indonesian citizen ex-combatants of the Islamic State Iraq and Syria (ISIS) in 2020. Repatriation issue becomes a dilemma for the government. Other hand, the government must be committed to protecting the human right of Indonesian ex-ISIS. Other hand, the government considers the security and safety aspects of millions of citizens from potential threats of Indonesian ex-ISIS. This study uses qualitative method in analysing the case study of government policy. By collecting various secondary dates in journals, media, and legal documents. The result indicates that the calculation of profit and loss between repatriate or not repatriate has been passed by the Indonesian government. In the process, the government finally rejected that Indonesia ex-ISIS has a goal for Indonesia’s national interest to protect the security of millions of citizens from the threat of terrorism.AbstrakPenelitian ini bertujuan menganalisis kebijakan pemerintah Indonesia menolak repatriasi warga negara Indonesia (WNI) eks Islamic State Iraq and Syria (ISIS) dari Suriah tahun 2020. Isu repatriasi ini menjadi dilema bagi pemerintah Indonesia. Di satu sisi pemerintah harus komitmen terhadap perlindungan hak asasi manusia (HAM) WNI eks ISIS. Di sisi lain mempertimbangkan aspek keamanan dan keselamatan warga negaranya dari potensi ancaman WNI eks ISIS. Penelitian ini menggunakan metode kualitatif dalam menganalisis studi kasus kebijakan pemerintah tersebut. Dengan menghimpun berbagai data-data sekunder yang tersebar di jurnal, media, dan dokumen-dokumen legal. Hasil penelitian ini menunjukkan bahwa kalkulasi untung rugi antara kebijakan memulangkan atau tidak memulangkan telah dilakukan oleh pemerintah Indonesia. Dalam proses pengkajian, pemerintah akhirnya menolak WNI eks ISIS karena lebih menguntungkan. Pertimbangan penolakan repatriasi WNI eks ISIS memiliki tujuan untuk kepentingan nasional Indonesia yakni untuk menjaga keamanan jutaan warga negara dari ancaman terorisme.